A graduate recital in wind band conducting: featuring analysis of Malcolm Arnold's Four Scottish Dances, arr. John Paynter, Marion Gaetano's Mosaic, Op. 30 for percussion octet, and Joan Tower's Celebration Fanfare from "Stepping Stones," arr. Jack Stamp - Maughlin, Ashley Marie (Kansas State University, 2009)
This document was submitted to the Graduate School of Kansas State University as a partial requirement for the Master’s of Music Education degree. It contains information about music education philosophy, what defines quality literature, theoretical and historical analyses, and rehearsal plans for each of the three pieces that were performed on the Graduate Student Conducting Recital on Wednesday, March 11, 2009. Selections performed on the recital included in the document’s analysis portion include Four Scottish Dances by Malcolm Arnold, arranged by John Paynter, Mosaic, Op. 30 by Mario Gaetano, and Celebration Fanfare from “Stepping Stones” by Joan Tower, arranged by Jack Stamp. The analytical methods employed in this document and the rehearsal techniques listed are based on the Blocker/Miles unit studies and macro-micro-macro concepts from the Teaching Music Through Performance in Band book series.
Keywords: Four Scottish Dances; Malcolm Arnold, arr. John Paynter; Mosaic, Op. 30; Mario Gaetano; Celebration Fanfare from Stepping Stones; Joan Tower, arr. Jack Stamp; Music (0413)